¿Responsabilidad sin responsabilización? En torno a los fundamentos normativos del enfoque interpersonal. Comentario a Adscripción y reacción de Sebastián Figueroa - Parmigiani , Matías (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The aim of this paper is to critically analyze the interpersonal approach to responsibility that Figueroa presents in Chaps. II, III and IV of Adscripción y reacción, but which he defends throughout his work. Whereas this approach might be identified as an exemplar of descriptive analytic philosophy, the argument here will be that it would have much more to gain if it decidedly assumes a normative purpose.